2002
DOI: 10.1007/s00167-001-0273-8
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between type of discoid lateral menisci and tear pattern

Abstract: This study analyzed the relationship between type of discoid lateral menisci and tear pattern. There were 108 consecutive cases (103 patients) with discoid lateral meniscus tear treated by arthroscopy. Regarding type of discoid meniscus (Watanabe's classification), 38 cases were "complete" and 70 cases "incomplete." There was no Wrisberg type. Tear patterns were classified into simple horizontal, complicated horizontal, longitudinal, radial, degenerative, and complex tear. The relationship between tear pattern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
87
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(91 citation statements)
references
References 13 publications
3
87
1
Order By: Relevance
“…The proportion of Wrisberg type meniscus has been reported to be between 0% and 33% [6,8,10,12,[20][21][22] and we found four patients (4 knees, 2.4%) with it. For bilateral occurrence, Bellier et al [2] reported 20% of patients with a discoid meniscus, Bin et al [3] reported 4.9%, and our result was 3.8% (six patients).…”
Section: Discussionmentioning
confidence: 43%
See 2 more Smart Citations
“…The proportion of Wrisberg type meniscus has been reported to be between 0% and 33% [6,8,10,12,[20][21][22] and we found four patients (4 knees, 2.4%) with it. For bilateral occurrence, Bellier et al [2] reported 20% of patients with a discoid meniscus, Bin et al [3] reported 4.9%, and our result was 3.8% (six patients).…”
Section: Discussionmentioning
confidence: 43%
“…1 Schematic drawings of the modified Watanabe's classification for lateral meniscal variants: a a complete meniscus, b an incomplete meniscus, c a Wrisberg meniscus, and d ringshaped meniscus dial tear includes a flap and an oblique tear. When the horizontal tear was accompanied by another tear component, extent of meniscal resection depended mainly upon the latter according to Bin et al [3]; hence we subdivided horizontal tears into simple and combined horizontal tear groups. Also, we proposed a new tear Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hayashi et al 10 reported that the longitudinal tear is the most common type of discoid meniscus damage. However, Smilie 12 and Bin et al 24 stated that the horizontal cleavage injury is the most frequent type, and this injury mostly occurs as a degenerative tear and might be presented as an apparently invisible substantial tear. Moreover, a study by Ferrer-Roca and Vilalta 25,26 indicates that the degenerative horizontal cleavage most frequently occurs in the middle portion of the meniscus just at the portion of the discoid meniscus containing the MPB.…”
Section: Discussionmentioning
confidence: 99%
“…Discoid meniscus is complicated by various tear patterns but there is no consensus regarding the relationship between the discoid anomaly type and tear type [9,20,42].…”
Section: Introductionmentioning
confidence: 99%